2020
DOI: 10.1111/ijfs.14620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on flow behaviour and physical properties of semi‐ripe plantain (AAB Musa spp) powders

Abstract: This work was conducted to study the influence of particle size and shape on the flow behaviour of semiripe plantain powders. An improved plantain variety (Big Ebanga), two hybrids (FHIA 21 and PITA 3), and a local variety (Corne 1, as reference material) were powdered by successive drying, milling, and sieving into three granulometric classes: unsieved (<500 µm), fine fraction (<180 µm; class 1), and coarse fraction (between 180 and 500 µm; class 2), thus differing in particle size distribution. Physical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Results also showed that pin‐milled flour was the most sensitive to aeration due to higher AeR (12.94) and highest normalized aeration sensitivity (0.26), which may be explained by its greater proportion of smaller particles as compared to other flours. In general, less cohesive powders have lower aerated energy and higher AeR and normalized aeration sensitivity (Irie et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Results also showed that pin‐milled flour was the most sensitive to aeration due to higher AeR (12.94) and highest normalized aeration sensitivity (0.26), which may be explained by its greater proportion of smaller particles as compared to other flours. In general, less cohesive powders have lower aerated energy and higher AeR and normalized aeration sensitivity (Irie et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…They are also critical factors for shelf [26]. The low content of the foutou flours between 6:09 and 8:33 < 14%, and the values of a w < 0:6 which represents the limit threshold of growth of microorganisms (yeasts, molds, bacteria) show that our flours present good aptitudes for conservation and storage at room temperature [20,27]. Indeed, at these values of water content and a w , our flours can be considered biochem-ically and microbiologically stable.…”
Section: Discussionmentioning
confidence: 86%
“…Water activity (a w ) of flour samples was determined using the HygroPalm water activity-meter (HP23AW-A, Rotronic, Croissy-Beaubourg, France) by the method described by Irie et al [20].…”
Section: Methodsmentioning
confidence: 99%
“…This characteristic is pivotal in ensuring efficient and cost-effective production processes within the food industry. As consumers increasingly demand powdered food products for their convenience and longer shelf life, optimizing powder flow becomes a critical factor for manufacturers [1]. The ability of powders to flow seamlessly through equipment not only influences the overall manufacturing efficiency but is also involved in affecting the consistency and quality of the final product.…”
Section: Introductionmentioning
confidence: 99%